Prevalence of Gingival Inflammation among Patients Taking Antipsychotic Drugs - Ayesha Rafique, Muhammad Iftikhar Ahsen, Muhammad Usman Khattak, Muhammad Yousaf Ali, Sittara Javed, Qasim Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To explore the prevalence and severity of gingival inflammation among the patients taking antipsychotic drugs. Method: This cross-sectional study was conducted in OPD of a psychiatric department of a tertiary care hospital in Lahore, Pakistan. Sample of 1025 patients was taken with the history of antipsychotic drugs. Patients were examined for the prevalence and severity of gingival inflammation and periodontal disease using modified gingival index (MGI) and basic periodontal examination (BPE). Study was conducted from March to August 2022. Data will be entered in SPSS version 25.0. Descriptive statistics, i.e. frequency and percentage were calculated for categorical data. Results: A total number 1025 patients with history of antipsychotic drugs were examined, 873 of them had some degree of gingival inflammation. Out of 873 patients with gingival disease, 536 (61.39%) patients exhibited mild to moderate inflammation whereas periodontal status of 337 (38.60%) patients presented severe inflammation. Basic periodontal examination was performed on individuals exhibiting severe gingival inflammation and patients were guided regarding further treatment that was needed to improve periodontal health. Conclusion: The findings of current study revealed that patients who are on anti-psychotic drugs are at higher risk of developing gingival diseases due to reduced salivary flow and need advanced treatment for their periodontal condition. Keywords: Psychosis, gingival diseases, Dental caries, Self-esteem